Modelling association factors of the Systemic Lupus Erythematosus (SLE) disease activity / Afiqah Roshidi, Khairunnisa Athirah Kamarudin and Nur Fatin Jaafar - Roshidi, Afiqah; Kamarudin, Khairunnisa Athirah; Jaafar, Nur Fatin Jaafar (2017)
Objective: To identify the socio-demographic characteristics of patients with Systemic Lupus Erythematosus (SLE) and determine the associated risk factors of SLE disease activity (active and in-active disease) in Hospital Universiti Sains Malaysia (HUSM). Methods: This study was conducted by analyzing the data of patients in HUSM which have been diagnosed with SLE in the year of 2010 until 2015. We analyzed data on a total of 106 patients (93 females and 13 males) using proforma sheet to identify the associated factors of SLE.Descriptive statistics was used to determine the sosio-demographic characteristics of patients with SLE and logistic regression analysis for the odds of having active and in-active SLE disease. Results: The findings revealed a signifant associated factors of patient with active SLE disease in contrast with patient with in-active disease. Female patients constituted the majority among all the patients with female to male ratio of 7:1.They had mean age of 36.27±14.386 years and mean duration of disease was 10.43±9.115 years. Conclusions: Patients with active SLE disease documented to have a higher prevalence of SLE especially female patient. Factors such as Antinuclear Antibody (ANA), Anti-double Stranded DNA (Anti -dsDNA) , family history and gender were noted as the associated risk factors affecting SLE among SLE patients in HUSM, Kelantan.